Spasmodic Torticollis—A Multicentre Study on Behavioural Aspects III: Psychosocial Changes and Coping - T. Nickel; F. Heinen; C. E. Scheidt; O. Rayki; J. Wissel; W. Poewe; R. Benecke; T. Gasser; W. Oertel; R. Dengler; G. Deuschl (Behavioural Neurology)
Psychosocial changes in spasmodic torticollis (ST) affect predominantly social life, professional life and psychological well-being. Concerning social life, 84.6% of the patients felt that they attracted considerable public attention due to their neurological illness and 65% had reduced participation in social events. A substantial number of patients had retired from professional activities; others felt severely impaired in their working capacity. The psychosocial sequelae in ST, however, seemed to depend less on the neurological signs per se than on the physical symptoms and on coping. Depressive coping in particular emerged as a predictor of psychosocial distress.